Selection of water conservation alternatives in urban areas using the multicriteria approach - Egito, Tuane Batista do; Fontana, Marcele Elisa; Morais, Danielle Costa (Revista Eletrônica em Gestão, Educação e Tecnologia Ambiental, 2015)
The degradation and exploitation of water resources in urban areas has been the subject of much debate in environmental preservation committees. This is due to misuse of this resource due to increased population, the lack of conservation policy and the lack of a culture of resource conservation in urban areas. For this problem, it is necessary to search for alternatives that promote water conservation in these centers. Therefore, a model was developed to support multi-criteria decision to evaluate these alternatives. This model uses a method based on outranking approach, the PROMETHEE V, to assist the decision maker in selecting some alternatives of conservation and efficient use of water, considering the criteria surveyed by decision maker and the restrictions on the problem.